EFEKTIVITAS EXTRACORPOREAL MEMBRANE OXYGENATION (ECMO) SEBAGAI TERAPI OKSIGENASI PADA PASIEN COVID-19 DENGAN ARDS : TINJAUAN PUSTAKA SISTEMATIS DAN META ANALISIS - Selvina Indah Permatasari Hutauruk (2022)
Background: Coronavirus Disease-2019 (COVID-19) is a disease that attacks the respiratory organs due to infection from SARS-Cov-2. The viral invasion is able to damage cells in the lungs and heart which eventually causes several critical syndromes or symptoms known as Acute Respiratory Distress Syndrome (ARDS). The high incidence of mortality in COVID-19 patients with ARDS requires the development of effective management. At present, the effectiveness of Extracorporeal Membrane Oxygenation (ECMO) as the therapy of choice in COVID-19 patients with ARDS is uncertain. Several studies have been conducted regarding the safety of ECMO, but the efficacy is not yet known so that a clear description of safety and efficacy is needed to prove whether ECMO is effective against COVID-19 with ARDS. Methods: Researchers conducted a systematic review and meta-analysis of 12 journals by searching the literature using the Cochrane Library, ProQuest, PubMed, Science Direct, SAGEPub, and Google scholar. PICO strategy (P: COVID-19 with ARDS, I: ECMO with VV (Venovenous), VA (Venoarterial), VAV (Venoarterial-Venous), C: None, O: Mortality, Survival Rate, and Length of Stay) with PRISMA-P selection and journal assessment using the JBI Critical Appraisal Checklist. Data analysis using the application Review Manager 5.4 and Comprehensive Meta Analysis V3 through meta analysis. The combined effect will be significant if the p value < 0.05. Results: 12 selected journals with good and moderate categories with a sample size of 6,255 patients showed that the results of the study in the form of ECMO had a mortality rate of 38.3%, a survival rate of 48%, and reduced hospitalization for survivors compared to non-survivors by 8.17 (95% CI), -4.33;16.52) in the ICU and 19.30 (95% CI, 7.33;31.27) in the hospital. Conclusion: ECMO therapy has proven to be quite effective because there is a significant relationship between ECMO on mortality, survival rate, and length of ICU and hospital stay in COVID-19 patients with ARDS. Keywords: ECMO, COVID-19 Therapy, ARDS, Effectivity